2012
DOI: 10.2298/abs1201287t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ionizing (gamma) and non-ionizing (UV) radiation on the development of Trichogramma euproctidis (Hymenoptera: Trichogrammatidae)

Abstract: The potential of using gamma and ultraviolet radiation as an alternative treatment to increase the efficiency of Trichogramma euproctidis (Girault 1911) (Hymenoptera: Trichogrammatidae) was investigated in the laboratory. The developmental and adult stages of T. euproctidis were exposed to gamma radiation of different doses (0-30 Gy) and ultraviolet radiation of 254 nm wavelengths (UV-C) for different durations (0-10 min) to assess their effect on each of the instars and their potential in breaking the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Our different results could be attributed to our irradiation treatment being applied to the grains containing the eggs and larvae of weevils, while that Faruki et al (2007); and Ghanem and Shamma (2007) irradiated eggs and larvae in Petri plates, therefore receiving strong direct radiation. According to Tuncbilek, Ercan, and Canpolat (2012), the UV-C radiation has superficial action, thus not reaching the eggs and larvae that are mainly deep inside the grain, thereby indicating FERREIRA ET AL. | 3 of 7 its ineffectiveness as a practical pest-control treatment technique for these weevil immature stages, as observed in treatments 5 and 6 ( Figure 1a).…”
Section: Live and Dead Weevilsmentioning
confidence: 99%
“…Our different results could be attributed to our irradiation treatment being applied to the grains containing the eggs and larvae of weevils, while that Faruki et al (2007); and Ghanem and Shamma (2007) irradiated eggs and larvae in Petri plates, therefore receiving strong direct radiation. According to Tuncbilek, Ercan, and Canpolat (2012), the UV-C radiation has superficial action, thus not reaching the eggs and larvae that are mainly deep inside the grain, thereby indicating FERREIRA ET AL. | 3 of 7 its ineffectiveness as a practical pest-control treatment technique for these weevil immature stages, as observed in treatments 5 and 6 ( Figure 1a).…”
Section: Live and Dead Weevilsmentioning
confidence: 99%
“…The embryonic stage of an insect is thought to be a period of UV radiation sensitivity (Tilton & Brower, ). Several studies have shown that intense UV (especially UV‐B/C) radiation reduces egg hatching significantly, and the percentage of hatched eggs decreases with increasing duration of exposure (Guerra, Ouye & Bullock, ; Faruki et al ., ; Tuncbilek, Ercan & Canpolat, ). As Song et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some insects are sensitive for radition (Mazza et al, 2010) found that the Thrips were maximally sensitive to wavelengths between 290 and 330 nm. Some insects are different in their sensitive to radiation dependent on different stages such as Trichogramma euproctidis, (Tuncbilek et al, 2012) found that the developmental and adult stages of T. euproctidis were exposed to gamma radiation of different doses (0-30 Gy) and ultraviolet radiation of 254 nm wavelengths (UV-C) for different durations (0-10 min) to assess their effect on each of the instars and their potential in breaking the developmental cycle of the egg parasitoid. The adult and pupa stages were more radio resistant to both gamma and UV radiation.…”
Section: Length Of Coxa Femur Tibia and Tarsus Of Fore And Hind Legmentioning
confidence: 99%